Towards an understanding of self-directed language as a mechanism of behavior change: A novel strategy for eliciting client language under laboratory conditions. (June 2018) - Ladd, Benjamin O.; Garcia, Tracey A.; Anderson, Kristen G.
Abstract: Introduction: Change talk (CT) and sustain talk (ST) are thought to reflect underlying motivation and be important mechanisms of behavior change (MOBCs). However, greater specificity and experimental rigor is needed to establish CT and ST as MOBCs. Testing the effects of self-directed language under laboratory conditions is one promising avenue. The current study presents a replication and extension of research examining the feasibility for using simulation tasks to elicit self-directed language. Methods: First-year college students ( N  = 92) responded to the Collegiate Simulated Intoxication Digital Elicitation, a validated task for assessing decision-making in college drinking. Verbal responses elicited via free-response and structured interview formats were coded based on established definitions of CT and ST, with minor modifications to reflect the non-treatment context. Associations between self-directed language and alcohol use at baseline and eight months were examined. Additionally, this study examined whether a contextually-based measure of decision-making, behavioral willingness, mediated relationships between self-directed language and alcohol outcome. Results: Healthy talk and unhealthy talk independently were associated with baseline alcohol use across both elicitation formats. Only healthy talk during the free-response elicitation was associated with alcohol use at follow up; both healthy talk and unhealthy talk during the interview elicitation were associated with 8-month alcohol use. Behavioral willingness significantly mediated the relationship between percent healthy talk and alcohol outcome. Conclusions: Findings support the utility of studying self-directed language under laboratory conditions and suggest that such methods may provide a fruitful strategy to further understand the role of self-directed language as a MOBC. Highlights: Feasibility test for eliciting self-directed alcohol statements in the laboratory Healthy talk reliably elicited and measured in response to a simulation task Healthy talk associated with current and future alcohol use in college students Provides a novel strategy for testing self-direct language as a mechanism of change